Role-play as a pedagogical method to prepare students for practice: The students’ voice - Westrup, Ulrika; Planander, Agneta (Högre utbildning, 2013)
In this article we discuss how and why role-play supports students in gaining insights into complex leadership situations. We give voice to the students by illustrating their experiences in a role-playing activity involving a human resource management issue designed, performed, and evaluated as part of a management program. The results show that the role-playing supports the students by stimulating them to understand the issue from various perspectives, hence performing an overall change of perspectives. The role-playing exercise also enabled the students to create a collective understanding of the situation. The active social interactions and conversations of role-playing contributed to establishing a sense of community among the students. We argue that role-play could be a viable and forceful pedagogical method whereby teachers give their students the opportunity to prepare for practice. However, to implement role-play as an alternative method of learning requires that the method is a part of the institutional learning space.